A new species of Dendroblatta Rehn, 1916 from northern Brazil (Blattaria: Ectobiidae) collected in wasp nests - Lopes, Sonia Maria; Da Silva, Leonardo De Oliveira Cardoso (Zootaxa, 2013)
Currently sixteen species of Dendroblatta Rehn, 1916 are known, twelve of them occurring in Brazil. In this paper, one new species, D. spiculata sp. nov., is described from material collected from the Acre and Amazonas states in northern Brazil, in wasp nests. The new species differs from all other members of the genus by the male genitalia pieces. Illustrations of the genital pieces are presented. In Brazil, the genus is now known from the states of Acre, Amazonas, Bahia, Mato Grosso, Minas Gerais, Pará, Rio de Janeiro, and Rondônia.